Dietary ecology of extant guanaco (Lama guanicoe) from Southern Patagonia: seasonal leaf browsing and its archaeological implications - Rivals, Florent (2013)
The analysis of dietary traits of ungulates through tooth microwear and mesowear has been applied to archaeological sites to investigate seasonal changes in settlements by hunter-gatherers. In this paper we propose to test the hypothesis that tooth microwear (combined to mesowear) is able to indicate seasonality in the diet of extant ungulates in arid habitats (semi-deserts or steppe). The material analyzed comes from six faunal monospecific assemblages of guanaco (Lama guanicoe) resulting from a mass mortality event in winter 2000 near the Cardiel Lake in Southern Patagonia (Province of Santa Cruz, Argentina). Results indicate that the guanacos from the Cardiel Lake area are mixed feeders, and thus, have a diet that shifts seasonally. Moreover, results from our analysis support the hypothesis that tooth microwear is able to indicate seasonality in the diet of extant guanaco in arid habitats.